This delicious death - Cottingham, Kayla (Sourcebooks Fire, an imprint of Sourcebooks, 2023)
"When four best friends with a hunger for human flesh attend a music festival in the desert they discover a murderous plot to expose and vilify the girls and everyone like them. This summer is going to get gory."--Publisher's description